Do Investors Trade Too Much? - Odean, Terrance (American Economic Review, 1999)
Trading volume on the world’s markets seems high, perhaps higher than can be explained by models of rational markets. For example, the average annual turnover rate on the New York Stock Exchange (NYSE) is currently greater than 75 percent and the daily trading volume of foreign-exchange transactions in all currencies (including forwards, swaps, and spot transactions) is roughly one-quarter of the total annual world trade and investment flow (James Dow and Gary Gorton, 1997). While this level of trade may seem disproportionate to investors’ rebalancing and hedging needs, we lack economic models that predict what trading volume in these market should be. In theoretical models trading volume ranges from zero (e.g., in rational expectation models without noise) to infinite (e.g., when traders dynamically hedge in the absence of trading costs). But without a model which predicts what trading volume should be in real markets, it is difficult to test whether observed volume is too high. If trading is excessive for a market as a whole, then it must be excessive for some groups of participants in that market. This paper demonstrates that the trading volume of a particular class of investors, those with discount brokerage accounts, is excessive. Alexandros V. Benos (1998) and Odean (1998a) propose that, due to their overconfidence, investors will trade too much. This paper tests that hypothesis. The trading of discount brokerage customers is good for testing the overconfidence theory of excessive trading because this trading is not complicated by agency relationships. Excessive trading in retail brokerage accounts could, on the other hand, result from either investors’ overconfidence or from brokers churning accounts to generate commissions. Excessive institutional trading, too, might result from overconfidence or from agency relationships. Dow and Gorton (1997) develop a model in which money managers, who would otherwise not trade, do so to signal to their employers that they are earning their fees and are not “simply doing nothing.” While the overconfidence theory is tested here with respect to a particular group of traders, other groups of traders are likely to be overconfident as well. Psychologists show that most people generally are overconfident about their abilities (Jerome D. Frank, 1935) and about the precision of their knowledge (Baruch Fischhoff et al., 1977; Marc Alpert and Howard Raiffa, 1982; Sarah Lichtenstein et al., 1982). Security selection can be a difficult task, and it is precisely in such difficult tasks that people exhibit the greatest overconfidence. Dale Griffin and Amos Tversky (1992) write that when predictability is very low, as in securities markets, experts may even be more prone to overconfidence than novices. It has been suggested that investors who behave nonrationally will not do well in financial markets and will not continue to trade in them. There are reasons, though, why we might expect those who actively trade in * Graduate School of Management, University of California, Davis, CA 95616. This paper is based on my dissertation at the University of California-Berkeley. I would like to thank Brad Barber, Hayne Leland, David Modest, Richard Roll, Mark Rubinstein, Paul Ruud, Richard Thaler, Brett Trueman, and the participants at the Berkeley Program in Finance, the National Bureau of Economic Research behavioral finance meetings, the Conference on Household Financial Decision Making and Asset Allocation at The Wharton School, the Western Finance Association meetings, and the Russell Sage Institute for Behavioral Economics, and seminar participants at the University of California-Berkeley, the Yale School of Management, the University of California-Davis, the University of Southern California, the University of North Carolina, Duke University, the University of Pennsylvania, Stanford University, the University of Oregon, Harvard University, the Massachusetts Institute of Technology, Dartmouth College, the University of Chicago, the University of British Columbia, Northwestern University, the University of Texas, UCLA, the University of Michigan, and Columbia University for helpful comments. I would also like to thank Jeremy Evnine and especially the discount brokerage house which provided the data necessary for this study. Financial support from the Nasdaq Foundation and the American Association of Individual Investors is gratefully acknowledged. 1 The NYSE website (http://www.nyse.com/public/ market/2c/2cix.htm) reports 1998 turnover at 76 percent.